Identification of a De Novo Heterozygous Missense ACTB Variant in Baraitser–Winter Cerebrofrontofacial Syndrome - Nie, Kailai; Huang, Junting; Liu, Longqian; Lv, Hongbin; Chen, Danian; Fan, Wei (Frontiers in Genetics, 2022)
Baraitser-Winter cerebrofrontofacial syndrome (BWCFF, OMIM: 243310) is a rare autosomal-dominant developmental disorder associated with variants in the genes ACTB or ACTG1. It is characterized by brain malformations, a distinctive facial appearance, ocular coloboma, and intellectual disability. However, the phenotypes of BWCFF are heterogenous, and its molecular pathogenesis has not been fully elucidated. In the present study, we conducted detailed clinical examinations on a Chinese patient with BWCFF and found novel ocular manifestations including pseudo-duplication of the optic disc and nystagmus. Targeted gene panel sequencing and Sanger sequencing identified a de novo heterozygous missense c.478A>G (p.Thr160Ala) variant in ACTB. The mRNA and protein expression of ACTB was assessed by quantitative reverse transcription PCR and western blots. Furthermore，the functional effects of the pathogenic variant were analyzed by protein structure analysis, which indicated that the variant may affect the active site for ATP hydrolysis by the actin ATPase, resulting in abnormal filamentous actin organization in peripheral blood mononuclear cells. This discovery extends the ACTB variant spectrum, which will improve genetic counseling and diagnosis, and may contribute to understanding the pathogenic mechanisms of actin-related diseases.